Caracterização e classificação de solos em uma topossêquencia na sub-bacia do córrego Maria Casimira, Serra do Gandarela-MG - Matheus da Cruz Armond (2018)
The Maria Casimira Stream watershed, a tributary of the Piracicaba River watershed, is located at the Gandarela’s Sinclinal, in the municipality of Santa Bárbara, MG. Its area is 1524 hectares, where the community of André do Mato Dentro is inserted. It is of great relevance in the geographic context of the Serra because it represents a striking feature of the region with a great water heritage. It presents springs and streams from groundwater, soils over ferruginous formations and an important geological diversity for recording the dynamics of Brasilian’s lithology formation. This region is known for its historical mineral exploitation, mainly of iron and gold ores, constituting one of the most important mining regions of the country, in counterpoint to an area with great preservation of the natural resources and to areas of great scenic beauty. In this context, the objective of this work was to study the soil-landscape relations in the Maria Casimira Stream watershed, in André do Mato Dentro (MG). The specific objectives were: (i) to perform the classification of chosen soil profiles in the watershed of the Maria Casimira stream; (ii) to analyze and discuss the soil-landscape relationships of the study area, based on pedological, topographic, lithological and phyto-physiognomic attributes; (iii) characterize and discuss the physical-hydric relationship of the soils in the watershed. Five soil profiles were chosen by free walking based on morphological and lithology differences. The soils were submitted to chemical and physical analyses, sulfuric attack and fertility and classified according to the Brazilian Soil Classification System as “CAMBISSOLO HÁPLICO Perférrico latossólico”, “CAMBISSOLO HÁPLICO Tb Eutroférrico latossólico”, “CAMBISSOLO HÁPLICO Tb Distrófico latossólico” and two “CAMBISSOLO HÁPLICO Tb Distroférrico”, from the highest to the lowest point in a road. Soils were related to the environment by the geosystem unit, with the properties of relief, geology, slope, climate and use and occupation. The different lithologies, in general, had greater influence on the properties of the soils. In relation to the physical-hydric characterization, the soil samples were subjected to analysis of texture, structure, soil and particle density, mineralogy and organic matter, and moisture in the sandbox and WP4C psychrometer. The values of moisture retention varied significantly between the horizons of the soils and are related to the differences in the physical and morphological characteristics of the soils.